STRUCTURE OF AMPLITUDE CONSTITUTIVE EQUATIONS FOR NON-ELASTIC PIEZOELECTRIC SOLIDS UNDER HARMONIC LOADING - Карнаухов, Василь Григорович; Михайленко, Василь Васильович; Лущиков, Олександр Володимирович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In this paper the structure of amplitude constitutive equations for nonelastic piezoelectric solids under harmonic loading is analyzed under the hypotheses of one-frequency electromechanical oscillations and time-shift invariance of amplitudes.